Isolation, marine transgression and translocation of the bare‐nosed wombat (Vombatus ursinus). (21st March 2019) - Martin, Alynn; Carver, Scott; Proft, Kirstin; Fraser, Tamieka A.; Polkinghorne, Adam; Banks, Sam; Burridge, Christopher P.
Abstract: Island populations can represent genetically distinct and evolutionarily important lineages relative to mainland conspecifics. However, phenotypic divergence of island populations does not necessarily reflect genetic divergence, particularly for lineages inhabiting islands periodically connected during Pleistocene low sea stands. Marine barriers may also not be solely responsible for any divergence that is observed. Here, we investigated genetic divergence among and within the three phenotypically distinct subspecies of bare‐nosed wombats ( Vombatus ursinus ) in south‐east Australia that are presently—but were not historically—isolated by marine barriers. Using genome‐wide single nucleotide polymorphisms, we identified three genetically distinct groups (mainland Australia, Bass Strait island, and Tasmania) corresponding to the recognized subspecies. However, isolation by distance was observed in the Tasmanian population, indicating additional constraints on gene flow can contribute to divergence in the absence of marine barriers, and may also explain genetic structuring among fragmented mainland populations. We additionally confirm origins and quantify the genetic divergence of an island population 46 years after the introduction of 21 individuals from the Vulnerable Bass Strait subspecies. In the light of our findings, we make recommendations for the maintenance of genetic variation and fitness across the species range.